Characteristics and immune checkpoint status of radioiodine-refractory recurrent papillary thyroid carcinomas from Ukrainian Chornobyl Tissue Bank donors - Bogdanova, Tetiana; Rogounovitch, Tatiana I.; Zurnadzhy, Liudmyla; Mitsutake, Norisato; Tronko, Mykola; Ito, Masahiro; Bolgov, Michael; Chernyshov, Serhii; Gulevatyi, Serhii; Masiuk, Sergii; Yamashita, Shunichi; Saenko, Vladimir A. (Frontiers in Endocrinology, 2024)
Introduction The radioiodine-refractory (RAI-R) recurrent papillary thyroid carcinomas (PTCs) are more frequent in elderly patients and have an unfavorable prognosis. Data on the prevalence and characteristics of RAI-R recurrent PTCs in patients of young and middle age with or without a history of radiation exposure in childhood are poorly described. The aim of the current study was: i) to determine the frequency of RAI-R recurrent PTCs among donors of the Chornobyl Tissue Bank (CTB) and analyze the clinicopathological features of primary tumors (PTs), primary metastases (PMTSs), recurrent metastases (RMTSs) and risk factors for RMTS, and ii) to determine the immune checkpoint status (ICS) of the RAI-R recurrent PTCs and to assess the factors associated with ICS positivity. Methods Sixty RAI-R recurrent PTCs (46 exposed to radiation and 14 non-exposed, 2.5% of all cases registered with the CTB) from the Ukrainian patients aged up to 48 years were identified. Results The clinicopathological characteristics of the PTs moderately to weakly resembled those of the PMTS and RMTS from the same patients while the metastatic tissues were highly similar. The multivariate model of RMTS included the dominant solid-trabecular growth pattern of the PT, cystic changes, N1b metastases, and the probability of a causation (POC) of PTC by radiation as risk factors. Among these factors, the lateral PMTS (N1b) had the strongest effect. The longer period of latency (a POC component) was the second statistically significant characteristic. ICS percent agreement between the PT and RAI-R RMTS was 91.5%; 23.7% of PTs and 28.8% of RMTSs had positive ICS (positive PD-L1 tumor epithelial cells (TECs) and positive PD-L1/PD1 tumor-associated immune cells). ICS positivity of PTs was associated with pronounced oncocytic changes and high density of the p16INK4A-positive TECs in the invasive areas of PTs. In RMTSs, ICS positivity was associated with pronounced oncocytic changes and Ki-67 labeling index ≥ 4.5% of PTs, and the dominant solid-trabecular growth pattern, Ki-67 labeling index ≥ 7.6% and p16INK4A-positivity of RMTS. Discussion The findings are of clinical relevance and may be useful for developing individual treatment approaches for patients with RAI-R recurrent PTCs possibly involving immunotherapy.